Recent Advances on Nanocomposite Resists With Design Functionality for Lithographic Microfabrication - Martínez, E. D.; Prado, A.; Gonzalez, M.; Anguiano, S.; Tosi, L.; Salazar Alarcón, L.; Pastoriza, H. (Frontiers in Materials, 2021)
Nanocomposites formed by a phase-dispersed nanomaterial and a polymeric host matrix are highly attractive for nano- and micro-fabrication. The combination of nanoscale and bulk materials aims at achieving an effective interplay between extensive and intensive physical properties. Nanofillers display size-dependent effects, paving the way for the design of tunable functional composites. The matrix, on the other hand, can facilitate or even enhance the applicability of nanomaterials by allowing their easy processing for device manufacturing. In this article, we review the field of polymer-based nanocomposites acting as resist materials, i.e. being patternable through radiation-based lithographic methods. A comprehensive explanation of the synthesis of nanofillers, their functionalization and the physicochemical concepts behind the formulation of nanocomposites resists will be given. We will consider nanocomposites containing different types of fillers, such as metallic, magnetic, ceramic, luminescent and carbon-based nanomaterials. We will outline the role of nanofillers in modifying various properties of the polymer matrix, such as the mechanical strength, the refractive index and their performance during lithography. Also, the lithographic techniques employed for transferring 2D patterns and 3D shapes with high spatial resolution. The capabilities of nanocomposites to act as structural and functional materials in novel devices for photonics, electronics, magnetism and bioscience applications will be presented. Finally, we will conclude with a discussion of the current trends in this field and perspectives for its development in the near future.